King of the gypsies [videorecording (DVD)] - Hayden, Sterling, 1916-1986; Roberts, Eric, 1956-; Sarandon, Susan, 1946-; Shields, Brooke, 1965-; Potts, Annie; Maas, Peter, 1929-2001 (Olive Films, 2015)
A compelling tale of New York's 'gypsies' and their criminal underworld. Dave, the grandson and heir apparent to the dying 'King', is torn between his legacy and the outside world, and is soon faced with a decision that will forever alter his life and the lives of those around him.